PENGARUH KEKUATAN IMPAK DAN TARIK KOMPOSIT BERPENGUAT SERAT SEMBUKAN DENGAN MATRIK EPOXY - Sinarep; Maulana, A.A.; Pandiatmi, Pandri; Zainuri, A (Energy, Materials and Product Design, 2024)
Composite is a combination of two or more elements arranged in a certain way to get new properties in matrial. Plants of Pukan (Peaderiafoetida L.) is a kind of wild grass that spreads and grows wild in nature. This study aims to determine the effect of the mechanical strength of the composite reinforced dying in the Healing with epoxy matrix. In this test, using Sembukan fiber as a reinforcement and epoxy as a composite matrial adhesive. The tests include: Tensile tests referring to ASTMD 3039, and Impact Tests referring to ASTMD 256. These tests use fiber volume fractions of 20%, 30%, and 40% with woven fiber orientation. The results showed, the greater the fiber volume fraction, the greater the toughness, the highest toughness was found in the fiber volume fraction variance of 40%, amounting to 0.10396 J/mm2. Same as Tensile testing, the stress increases with increasing fiber volume fraction, ie at 40% fiber at 9,1596 MPa. The influencing factor is none other than the percentage of fibers in the composite increasing the mechanical strength of the matrix. Keywords: Fiber Heal, toughness Impact, Tensile strength.